PURCHASE BEHAVIOR IN MAKING DECISION IN SMALL AND MEDIUM-SIZED ENTERPRISES IN SERVICE SECTOR FOR INNOVATIVE SOLAR POWER AIRCONDITIONING SYSTEM - Thitakom Leetanan; Thapong Teerawatananond; Amnuay Saengnoree; Samart Deebhijarn (Journal of Namibian Studies History Politics Culture, 2023)
This article aims to explore consumer behavior in purchasing decisions of solar air conditioning innovations of small and medium enterprises (SMEs) in the service sector. From the study of the concept related theory, it can be concluded that consumer behavior in purchasing decisions of solar air conditioning innovations of small and medium enterprises in the service sector consisted of Government Policies, Product feature Innovations, Consumer Innovation, Consumers Perceived Value.
Keywords: Sustainability, Governance, and Employment Studies; SMEs Development and Digital Marketing; Employee Performance and Management